A highly virulent variant of HIV-1 circulating in the Netherlands - Wymant,C; Bezemer,D; Blanquart,F; Ferretti,L; Gall,A; Hall,M; Golubchik,T; Bakker,M; Ong,SH; Zhao,L; Bonsall,D; de,Cesare M; et al. (Science, 2022)
Changes in viral load and CD4+ T cell decline are expected signals of HIV evolution. By examining data from well-characterized European cohorts, Wymant et al. report an exceptionally virulent subtype of HIV that has been circulating in the Netherlands for several years (see the Perspective by Wertheim). More than one hundred individuals infected with a characteristic subtype B lineage of HIV-1 were found who experienced double the rate of CD4+ cell count declines than expected. By the time they were diagnosed, these individuals were vulnerable to developing AIDS within 2 to 3 years. This virus lineage, which has apparently arisen de novo since around the millennium, shows extensive change across the genome affecting almost 300 amino acids, which makes it hard to discern the mechanism for elevated virulence. —CA